(untitled) (Scientific journal of the Fergana State University, 2025)
The chemical compositions of the waters from Chortoq and Kirkidon water reservoirs in the Fergana Valley were studied for the cultivation of the aquatic plant Chlorella vulgaris. The analysis included parameters such as CI-, Fe++, F+, -NH4+, NO2-, NO3-, as well as mineralization and hardness. The pH was also examined.